2022
DOI: 10.3390/jpm12020202
|View full text |Cite
|
Sign up to set email alerts
|

DNA Methylation and Asthma Acquisition during Adolescence and Post-Adolescence, an Epigenome-Wide Longitudinal Study

Abstract: The role of epigenetics in the pathogenesis of asthma acquisition in adolescence and post-adolescence has been unknown. We carried out a longitudinal epigenome-wide association study, using data from the Isle of Wight Birth Cohort (IOWBC). To improve statistical power, we first screened CpGs based on associations of DNA methylation (DNAm) at an age of 10 years (pre-adolescence) with asthma acquisition at 10–18 years (during adolescence). A logistic regression with repeated measures was applied to CpGs that pas… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 57 publications
0
6
0
Order By: Relevance
“…However, a potential increase in our understanding of asthma may lie in investigating the disease to some longitudinal capacity. Two previous studies in the Isle of Wight Birth Cohort (IOWBC) were conducted in 2022, which investigated the association of DNA methylation with asthma acquisition across adolescence and adulthood [44,45]. In each of these studies, several CpGs, with some residing in immune regulatory genes, were identified to be associated with asthma acquisition [44,45].…”
Section: Discussionmentioning
confidence: 99%
“…However, a potential increase in our understanding of asthma may lie in investigating the disease to some longitudinal capacity. Two previous studies in the Isle of Wight Birth Cohort (IOWBC) were conducted in 2022, which investigated the association of DNA methylation with asthma acquisition across adolescence and adulthood [44,45]. In each of these studies, several CpGs, with some residing in immune regulatory genes, were identified to be associated with asthma acquisition [44,45].…”
Section: Discussionmentioning
confidence: 99%
“…Hongmei Zhang 2 Hasan Arshad 3,4,5 Susan Ewart 6 Meredith Ray 2 Caroline L. Relton 7,8,9 Wilfried Karmaus 2 John W. Holloway…”
Section: Data Ava I L a B I L I T Y S Tat E M E N Tmentioning
confidence: 99%
“…3 DNA methylation (DNAm) or longitudinal change in DNAm at specific cytosine-phosphate-guanine (CpG) sites is associated with the risk of both atopy and asthma 4,5 or asthma acquisition. 6 The role of atopy in the association of DNAm in newborns with asthma acquisition at a later age is unknown. Utilizing data in the Isle of Wight Birth Cohort (IOWBC), we examined whether pre-adolescence atopy mediates the association of newborn DNAm with asthma acquisition from pre-to post-adolescence.…”
Section: The Association Of Dna Methylation At Birth With Adolescent ...mentioning
confidence: 99%
“…DNAm has been shown to be associated with childhood asthma [ 6 , 7 ]. Furthermore, our previous findings suggested a potential association between DNAm at birth and the acquisition of asthma during adolescence [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…By examining individual CpG sites and differentially methylated regions at birth, eight CpG sites were identified as potential epigenetic biomarkers for asthma acquisition during adolescence [ 15 ]. Another study that investigated the association between DNA methylation at birth and asthma acquisition showed that the associated CpGs were more likely to be different between genders and may also be unique to specific transition periods [ 8 ]. Additionally, a separate study highlighted the role of atopy as a mediator in the relationship between DNA methylation and asthma development during both pre- and post-adolescence [ 16 ].…”
Section: Introductionmentioning
confidence: 99%